Materialidades de um processo de circulação de ideias na ciência - Ilha, Gisandro Cunha (2019)
Based on the epistemology of Ludwik Fleck, we seek in this work to construct an analytical-conceptual device of reference that allows to study the processes of constitution of the scientific knowledge from the epistemological category Style of Thought of Fleck. For its implementation we use the theoretical precepts of French Speech Analysis, affiliated to Michel Pêcheux, especially using the concept of Discursive Formation, not disregarding the contribution of Michel Foucault in its structuring. As object of analysis we consider certain scientific articles, published in three Brazilian scientific journals, that deal with the teaching of chemistry in the perspective of the history and philosophy of science. In order to achieve the study proposal, at the outset, we composed the bases that allowed the founding of the analytical device designed, bringing as a point of support the theoretical architecture Style of Thought / Discursive Formation, seeking to arrive at the materiality of a possible Style of Thought a from the discursive materialities, obtained in the analysis of the scientific articles that composed the archive of this research. As a practical result, we could point to the existence of a collective still without a sufficiently structured Thinking Style (in history and philosophy from a teaching-learning chemistry perspective) that allows it to exert a coercive force enough to keep its members united around of what Fleck would consider a Stable Collective of Thought. We also point to the assumption of the materiality of a Style of Thought considered from the discursive materialities and not as an a priori taken from any collective supposedly characterized as being of the utmost importance, through the dynamics of analysis proposed and defended here a Collective of Thought.